2023
DOI: 10.3390/microorganisms11020280
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analysis and In Vitro Investigation of the Hop Resistance Phenotype of Two Novel Loigolactobacillus backii Strains, Isolated from Spoiled Beer

Abstract: Loigolactobacillus backii is an important beer-spoiling species, exhibiting high hop tolerance. Here, we present the annotated whole genome sequence of two recently isolated strains, Lg. backii KKP 3565 and KKP 3566. Firstly, to study the genetic basis of the persistence of the two isolates in beer, a comprehensive bioinformatic analysis ensued. Their chromosome map was constructed, using whole-genome sequencing and assembly, revealing that the two strains carry genomes with a length of 2.79 Mb with a GC conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…Detection at the strain level can give definite evidence for the presence of spoilage strains [16] and discriminate against members of the same species with no harmful activity while also providing hints at appropriate decontamination methods. In this vein, we have previously shown that contaminant Loigolactobacillus backii strains are resistant to heat stress but may be sensitive to pressure treatment, resulting in more efficient decontamination approaches in the brewing industry [46]. Importantly, the novel method developed does not require a high level of technical expertise or sophisticated equipment; it can, therefore, be easily employed in the setting of the fermented food industry.…”
Section: Discussionmentioning
confidence: 99%
“…Detection at the strain level can give definite evidence for the presence of spoilage strains [16] and discriminate against members of the same species with no harmful activity while also providing hints at appropriate decontamination methods. In this vein, we have previously shown that contaminant Loigolactobacillus backii strains are resistant to heat stress but may be sensitive to pressure treatment, resulting in more efficient decontamination approaches in the brewing industry [46]. Importantly, the novel method developed does not require a high level of technical expertise or sophisticated equipment; it can, therefore, be easily employed in the setting of the fermented food industry.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the resistance to hop, the growth kinetics of the KKP 3573 strain was estimated with the automated growth curve analysis system Bioscreen C Pro (Oy AB Ltd., Growth Curves, Finland), as described by Kiousi et al, 2023 [ 25 ]. London Ale beer was used to formulate the starting concentration of 40 IBU, from which other IBU concentrations—5, 10, 20, and 30—were prepared to perform hop resistance analysis on the Bioscreen.…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA from the KKP 3573 strain was isolated using DNeasy PowerFood Microbial Kit (Qiagen, GmbH, Hilden, Germany) according to the manufacturer’s protocol and as described by Kiousi et al, 2023 [ 25 ]. Briefly, DNA purity was determined with Nanodrop ND-1000 Spectrophotometer (Thermo Fisher Scientific, Watertown, MA, USA), and DNA concentration was measured with Qubit 4.0 Fluorometer (Qubit dsDNA BR Assay Kit, Invitrogen, Carlsbad, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The genome of bacterial strains contained inserts from other contagious species. These genetic constructs contribute to the adaptation of representatives of lactic acid bacteria to the harsh environment of the brewery, including carrying out vital activities at high concentrations of hops [55]. A similar study, in which lactic acid bacteria were identified in beer, was carried out using the PCR method with primers for the hop resistance genes horA and horC.…”
Section: Microorganisms In Beermentioning
confidence: 99%